2012
DOI: 10.1177/2150131912446374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Standardized All-Terrain Vehicle Safety Education Intervention for Youth in Rural Central Illinois

Abstract: This safety program was effective at increasing ATV safety knowledge but demonstrates limited effect on safe riding practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…As discussed above, three contraindicated behaviours, youth aged <16 years riding adult-sized ATVs, non-use of helmets, and allowing passengers, are quite common among young ATV riders. Furthermore, ATV crashes are common,11 14 17 30 and most do not result in serious injury. For example, two-thirds of young riders in Illinois reported having crashed an ATV during the past 6 months, with 11% of those injured requiring medical care 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, three contraindicated behaviours, youth aged <16 years riding adult-sized ATVs, non-use of helmets, and allowing passengers, are quite common among young ATV riders. Furthermore, ATV crashes are common,11 14 17 30 and most do not result in serious injury. For example, two-thirds of young riders in Illinois reported having crashed an ATV during the past 6 months, with 11% of those injured requiring medical care 11.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern persists despite the CPSC's recommendation that children aged ≤15 years not ride or drive adult-sized ATVs29 and a voluntary agreement by ATV manufacturers and distributors “to use their best efforts to prevent their dealers from selling adult-sized ATVs for use by children under the age of 16” 26. Additionally, surveys of young ATV riders report that riding as a passenger or allowing others to ride as a passenger is common 11 12 17 30Youngest children from large families more at risk of fractures

A study from Nottingham based on the same database as that described above, concluded that children under 5 years old are more likely to fracture bones in their arms and legs if they were older than one, had older brothers or sisters, had young mothers or mothers with a history of alcohol misuse.

…”
Section: Discussionmentioning
confidence: 99%
“…4,5,22,23,26,28,29 Safety training is important for these youth who may often lack even basic ATV safety knowledge. 23,[30][31][32] Injury prevention also requires getting these adolescents off adult-sized vehicles and off roadways, and the Y12+ and Y14+ models must be evaluated with respect to the safety of speed standards. If children in this age group are allowed to ride ATVs, parents need to set strict safety guidelines, carefully monitor riding behaviors, and appropriately respond when safety behavior expectations are violated.…”
Section: To 15 Years Of Agementioning
confidence: 99%
“…However, another school-based educational program in the rural U.S. demonstrated the disconnect that may exist between knowledge enhancement and behavioural change. Although the youth in this particular study demonstrated a significant increase in knowledge regarding ATV safety, there was not an associated effect on safe riding practices [22]. The authors suggested that in the future the design and implementation of a community-based multi-agency ATV injury prevention intervention should include parents in order to improve its impact, specifically on behavioural risks.…”
Section: Does Education Make Atv Riders Safer?mentioning
confidence: 78%